Предмет: Алгебра,
автор: ololowka1212
3*(2х-3/х+1)^2-44х-66/х+1+7=0решить уравнение,используя замену неизвестного
Ответы
Автор ответа:
0
Пусть 2х-3/x+1 = t
3t^2 - 22t + 7 = 0
D1 = 121 - 21 =100 =10^2
t1 = (11 + 10)/3 = 7
t2 =(11-10)/3 = 1/3
Выполним обратную замену:
t1 = 7 => 2x-3/x+1 = 7 => x = -2
t2 = 1/3 => 2x - 3/x+1 = 1/3 => x = 2
3t^2 - 22t + 7 = 0
D1 = 121 - 21 =100 =10^2
t1 = (11 + 10)/3 = 7
t2 =(11-10)/3 = 1/3
Выполним обратную замену:
t1 = 7 => 2x-3/x+1 = 7 => x = -2
t2 = 1/3 => 2x - 3/x+1 = 1/3 => x = 2
Похожие вопросы
Предмет: Математика,
автор: musaaleksandr483
Предмет: Математика,
автор: 2008halrost
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: фалькао
Предмет: Биология,
автор: Азиз770